2018
DOI: 10.1016/j.celrep.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Promote Apelin-Mediated Sprouting Angiogenesis in Type 2 Diabetes

Abstract: The role of CD4 T cells in the ischemic tissues of T2D patients remains unclear. Here, we report that T2D patients' vascular density was negatively correlated with the number of infiltrating CD4 T cells after ischemic injury. Th1 was the predominant subset, and Th1-derived IFN-γ and TNF-α directly impaired human angiogenesis. We then blocked CD4 T cell infiltration into the ischemic tissues of both Lepr and diet-induced obese T2D mice. Genome-wide RNA sequencing shows an increased proliferative and angiogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 46 publications
4
66
0
1
Order By: Relevance
“…For instances, Burzyn et al reveal that Treg directly promote activation of satellite cells and regeneration of skeletal muscle via secretion of amphiregulin 9 ; Arpaia et al demonstrate that Treg facilitate tissue repair after influenza infection 12 ; Dombrowski et al unveil that Treg promote differentiation of oligodendrocytes and regeneration of myelin in the central nervous system 14 ; and Ali et al uncover that Treg facilitate proliferation and differentiation of hair follicular stem cells in skin 11 . More recently, we have also showed that Treg promote regeneration of blood vessels in the peripheral artery system after ischemic injury in type-2 diabetes 15 . In fact, targeting T-cells for tissue regeneration offers unappreciated advantages such as specificity towards autoantigens released during injury.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…For instances, Burzyn et al reveal that Treg directly promote activation of satellite cells and regeneration of skeletal muscle via secretion of amphiregulin 9 ; Arpaia et al demonstrate that Treg facilitate tissue repair after influenza infection 12 ; Dombrowski et al unveil that Treg promote differentiation of oligodendrocytes and regeneration of myelin in the central nervous system 14 ; and Ali et al uncover that Treg facilitate proliferation and differentiation of hair follicular stem cells in skin 11 . More recently, we have also showed that Treg promote regeneration of blood vessels in the peripheral artery system after ischemic injury in type-2 diabetes 15 . In fact, targeting T-cells for tissue regeneration offers unappreciated advantages such as specificity towards autoantigens released during injury.…”
Section: Discussionmentioning
confidence: 84%
“…There was a significant increase in %CD4 + FOXP3 + Treg among CD4 + T-cells (Fig 3B) or in absolute number of CD4 + FOXP3 + Treg per mg tissue (Fig 3C) at day 7 post CI compared to sham. We then depleted CD4 + CD25 hi FOXP3 + Treg via the lytic anti-CD25 antibodies (clone PC61) as previously described (Fig 3D, Fig S2) 15,19 . Treatment with PC61 significantly increased cardiac fibrosis (Fig 3E, F) and COLA1 deposition (Fig 3G); and significantly reduced cTnT + myocardium in the infarct zone (Fig 3G, H) and lessened Ki67 + cTnT + proliferating cardiomyocytes in the border zone at day 28 post CI (Fig 3I, J).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations